Fundamentals epistemological of business administration: regional analysis induction to central - Gilberto J. P. Ceballos Ramírez, Flover Artunduaga Lizcano, Ricardo Parra Parra, (Opción, 2020)
This proposal reflects the need to identify the epistemological foundations of Administration in the University Corporation Minuto de Dios, doing an analysis of the periphery or regions where this institution develops programs of Business Administration, in order to generate certain principles consistent with the needs and requirements of the context, and then to review and complement regional approaches and epistemological theories with central or national and international recognition.  AbstracLa presente propuesta obedece a la necesidad de identificar los fundamentos epistemológicos de la Administración en la Corporación Universitaria Minuto de Dios, haciendo un análisis que parte de la periferia o las regiones donde esta institución desarrolla los programas de Administración de Empresas, con el fin de generar ciertos postulados acordes con las necesidades y requerimiento del contexto, para luego hacer una revisión y complementación de estos planteamientos epistemológicos regionales con teorías centrales o de reconocimiento nacional e internacional.